Erwin Rommel and German Military Doctrine, 1912–1940. (July 2017) - Samuels, Martin
Rommel's approach to command and his relationship with the German army's doctrine remain subjects of lively debate. Analysis of his career prior to 1940 shows he was a highly respected figure at the centre of the army's officer training system. Consideration of his approach during the crossing of the Meuse in May 1940 demonstrates consistency with his actions at Caporetto in 1917. Far from proving his unorthodoxy, however, comparison of this approach with the army's official manuals suggests Rommel acted fully in accordance with doctrine. This highlights a tension within that doctrine between independence of action and wilfulness.